Prevention of Postoperative Purulent-Inflammatory Complications Using Photodynamic Therapy in Strangulated Hernias - Khasan Jafarov; Tohir Askarov; Shuxrat Isakov; Erkin Zakhidov; Mukhibjon Imomov; Arzayim Sabirova; Ansatbay Jambulov (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Postoperative infectious complications remain a major challenge in abdominal surgery, particularly in cases of strangulated abdominal hernias where microbial contamination of the surgical field frequently occurs. Specific Background: Photodynamic therapy using photosensitizers and light activation has been proposed as an antimicrobial approach, while methylene blue represents an accessible and low-cost photosensitizer that can be activated by LED irradiation. Knowledge Gap: Despite its potential advantages, the clinical and microbiological role of methylene-blue–mediated photodynamic therapy in preventing postoperative purulent-inflammatory complications in strangulated hernia surgery has not been sufficiently investigated. Aims: This study aimed to evaluate the microbiological characteristics of hernial sac infections and assess the preventive potential of intraoperative photodynamic therapy using methylene blue and LED irradiation. Results: A comparative clinical study of 225 patients showed that hernial sac infections were predominantly polymicrobial, with Escherichia coli (46%), Staphylococcus aureus (28%), and Staphylococcus epidermidis (6%) being the most common pathogens. Combined photodynamic treatment reduced microbial contamination from 10⁴ CFU/ml to 10² CFU/ml and lowered postoperative complications from 16.3% in the control group to 6.3% in the treated group, while also shortening hospital stay from 10.0 ± 0.67 days to 7.3 ± 0.77 days. Novelty: The study demonstrates the clinical and microbiological benefits of intraoperative photodynamic sanitation using methylene blue and LED light in strangulated hernia surgery. Implications: The findings support the use of accessible photodynamic techniques as a practical strategy for reducing postoperative purulent-inflammatory complications and improving surgical outcomes. Highlights:• Significant Decrease in Bacterial Contamination After Intraoperative Photodynamic Sanitation• Lower Frequency of Postoperative Purulent-Inflammatory Events in Treated Patients• Shorter Hospitalization Period Following Methylene-Blue–Based Photodynamic Treatment Keywords: Photodynamic Therapy, Strangulated Hernia, Methylene Blue, Surgical Site Infection, Postoperative Complications.